2020
DOI: 10.21203/rs.3.rs-79141/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective online professional development: Teacher perceptions, practices, and preferences

Abstract: Never before has the importance of effective online professional development been more prominent than it has during the COVID-19 times with the significant transition to working and teaching online. Effective professional development (PD) is critical in supporting in-service teachers to continue developing professionally, expanding their knowledge, skills, and abilities, and enhancing self-efficacy. The elements of effective face-to-face PD have been researched extensively, but those for online PD remain elusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
3
1
2
1
Order By: Relevance
“…The statistical results of the current study seem to reveal that teachers tend to show higher preference for traditional forms of professional development (75.73%) than for the online forms (24.27%). These findings are in sharp contrast to a number of studies in which teachers preferred online professional development due to its flexibility and sustainability (Poole et al, 2020;Reeves & Pedulla, 2011). However, in the Moroccan context there are many reasons behind the disfavor of face-to-face forms of professional development as reported by teachers who participated in this study.…”
Section: Teachers' Preferences Of Online Professional Development Activitiescontrasting
confidence: 99%
See 3 more Smart Citations
“…The statistical results of the current study seem to reveal that teachers tend to show higher preference for traditional forms of professional development (75.73%) than for the online forms (24.27%). These findings are in sharp contrast to a number of studies in which teachers preferred online professional development due to its flexibility and sustainability (Poole et al, 2020;Reeves & Pedulla, 2011). However, in the Moroccan context there are many reasons behind the disfavor of face-to-face forms of professional development as reported by teachers who participated in this study.…”
Section: Teachers' Preferences Of Online Professional Development Activitiescontrasting
confidence: 99%
“…This participation was in the form of using different tools of online professional development such as web-based activities, social networks, and online communities of practice. These findings are supported by previous studies in which teachers reported participating in online professional development using social networks, webinars, and online communities for professional development (Alzahrani & Althaqafi, 2020;Poole et al, 2020). However, the rate of teachers' participation in online professional development activities in this study (58.25%) is not significantly higher than those who did not participate (41.15%).…”
Section: Discussion Of the Findings 51teachers' Participation In Online Professional Development Activitiessupporting
confidence: 86%
See 2 more Smart Citations
“…On the other hand, teachers who had only taken face-to-face PDs were less eager to experience the online format. Such findings corroborate further research that has found OPDPs to be a highly effective PD tool, particularly during the pandemic (Berndt et al, 2017;Poole et al, 2020;Pradeep, 2021;Turcsányi-Szabó, 2008). Erickson et al (2012) further highlight that OPDP-trained teachers improved their capacity to incorporate research-based methods into their teaching practices.…”
Section: Literature Reviewsupporting
confidence: 87%